BLOOD PLASMA TRACE ELEMENTS IN REPEAT BREEDING MEHSANI BUFFALOES - PATEL, P A; SIDDIQUEE, G M; NAKHASHI, H C; SUTHAR, B N (The Indian Journal of Animal Reproduction, 2023)
Blood plasma trace mineral analysis indicated that the levels of blood plasma copper, iron, zincand manganese were significantly higher (P < 0.05) in normal fertile as compared to repeat breedingMehsani buffaloes at 0, 10th and 201h days post-estrus.
Keywords: Trace minerals; Repeat breeder; Buffalo